2019
DOI: 10.1097/md.0000000000016347
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure variability with different measurement methods

Abstract: Blood pressure variability (BPV) is an independent cardiovascular risk factor in hypertensive patients. The best method for quantifying BPV is still an object of debate. The existence of different BPV patterns, particularly age and arterial stiffness related, is postulated. Our aims were: to compare BPV using different blood pressure (BP) measurement methods to compare different calculation approaches to analyze the predictors of BPV. Cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Interestingly, in multivariable analysis, VIM of SBP showed a strong, negative linear relationship with TAC, independent of average SBP and DBP levels. Moreover, another study conducted on hospitalized elderly individuals with HTN has confirmed a positive correlation between the amplitude of beat-to-beat BP fluctuations, as assessed by ΔBP (the difference between maximum and minimum BP values), and vascular stiffness expressed by pulse wave velocity (PWV) [41]; large BP fluctuations were associated with lower vascular elasticity.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Interestingly, in multivariable analysis, VIM of SBP showed a strong, negative linear relationship with TAC, independent of average SBP and DBP levels. Moreover, another study conducted on hospitalized elderly individuals with HTN has confirmed a positive correlation between the amplitude of beat-to-beat BP fluctuations, as assessed by ΔBP (the difference between maximum and minimum BP values), and vascular stiffness expressed by pulse wave velocity (PWV) [41]; large BP fluctuations were associated with lower vascular elasticity.…”
Section: Introductionmentioning
confidence: 83%
“…Hence, the direct positive impact of lacidipine on effectors of beat-to-beat BPV was demonstrated [49]. A clinical study on elderly hypertensive individuals further confirmed the ameliorative effect of CCBs by showing a tendency for beat-to-beat SBPV to decrease with their use, although it increases with the use of diuretics [41]. A study on a normotensive rat model with increased beat-to-beat BPV revealed the presence of pleotropic effects specific to drug generations.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The use of the former is conceptionally more intuitive while the latter may be considered more robust because, by dividing within patient SD by their mean, a degree of random variation can be overcome. 25…”
Section: Discussionmentioning
confidence: 99%
“…The use of the former is conceptionally more intuitive while the latter may be considered more robust because, by dividing within patient SD by their mean, a degree of random variation can be overcome. 25 Importantly, these 2 measures are suitable to measure blood pressure variability in the context that clinic and 24-hour BPs were collected in this trial, whereas variation independent of the mean and the average real variability are less suitable in the context of limited clinic measures. Furthermore, the trends in BP variability across the 3 groups of patients were similar whether measured by SD or coefficient of variation.…”
Section: Discussionmentioning
confidence: 99%